Evolution of India-Nepal Relations from 2014 to 2024 - E. E. Novinskii (Научный диалог)
This article examines the bilateral relations between India and Nepal, which hold a unique status. On one hand, India perceives the mountainous nation not only as a culturally and civilizationally close neighbor but also as a vulnerable link in its security framework. On the other hand, Nepal endeavors to pursue a policy of balancing, striving to prevent the excessive strengthening of either neighbor’s influence within its borders. The study demonstrates that during the specified period, India has intensified its South Asian foreign policy under the “Neighborhood First” strategy. This has led to a significant increase in political contacts and a robust growth in economic interactions. However, it is revealed that frequent crises in relations, India's exertion of pressure, and the anti-Indian rhetoric of certain Nepali leaders have detrimental effects on the positive perception of bilateral ties within society. It is established that the Madhesi communities residing along the southern stretch of the India-Nepal border — most closely associated with India — are the most adversely affected by these dynamics. Furthermore, the article underscores the critical role of the Chinese factor in the evolution of bilateral relations, as China consistently strengthens its foothold in Nepal (and across South Asia). The analysis also illustrates how India responds to Beijing’s initiatives in the Himalayan state.